Peran Pemerintah Dalam Meningkatkan Perekonomian Indonesia Pada Masa Pandemi Covid-19 - Lathifah , Gendia Saumy; Prayoga, Ilham Dwi (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: The Covid-19 pandemic in Indonesia has paralyzed the Indonesian economy; many MSMEs have gone bankrupt because their income has decreased, and many companies have laid off their employees. This study aims to analyze several government policies to save the economy during the Covid-19 pandemic in Indonesia. Research Methods: This study uses qualitative data from articles, books, journals, or other related sources. Finding/Results: The results of the study show that to overcome the economic problems, the government has taken steps in the form of fiscal and monetary policies. Fiscal policies include the pre-employment card program, tax incentives, launching budget refocusing, and budget reallocation. Monetary policies such as MSME credit restructuring Bank Indonesia's rupiah stability. Conclusion: The government must make every effort to stabilize and improve the economic sector in Indonesia to improve people's welfare